Brain Ischemia Significantly Alters microRNA Expression in Human Peripheral Blood Natural Killer Cells - Kong, Ying; Li, Shiyao; Cheng, Xiaojing; Ren, Honglei; Zhang, Bohao; Ma, Hongshan; Li, Minshu; Zhang, Xiao-An (Frontiers in Immunology, 2020)
Brain ischemia induces systemic immunosuppression and increases host susceptibility to infections. MicroRNAs (miRNAs) are molecular switches in immune cells, but the alterations of miRNAs in human immune cells in response to brain ischemia and their impact on immune defense remain elusive. Natural killer (NK) cells are critical for early host defenses against pathogens. In this study, we identified reduced counts, cytokine production and cytotoxicity in human peripheral blood NK cells obtained from patients with acute ischemic stroke. The extent of NK cell loss of number and activity was associated with infarct volume. MicroRNA sequencing analysis revealed that brain ischemia significantly altered miRNA expression profiles in circulating NK cells, in which miRNA451a and miRNA122 were dramatically upregulated. Importantly, inhibition of miR451a or miR122 augmented the expression of activationassociated receptors in NK cells. These results provide the first evidence that brain ischemia alters miRNA signatures in human NK cells.